Changes in the Use of Emergency Care for the Youth With Mental Health Problems Over Decades: A Repeated Cross Sectional Study - Benarous, Xavier; Milhiet, Vanessa; Oppetit, Alice; Viaux, Sylvie; El Kamel, Nadjia Mahi; Guinchat, Vincent; Guilé, Jean-Marc; Cohen, David (Frontiers in Psychiatry, 2019)
To understand whether changes exist in the types of youths mental health problems addressed in emergency in a context of increasing demand, we conducted a retrospective chart review in an emergency care outpatient unit. Data from children and adolescents admitted at four different time periods (years 1981, 1992, 2002, and 2017) were compared to determine trends in terms of patients’ characteristics, nature of the mental health problems and final care decisions. Between 1981 and 2017 there was a 3.85 times increase in the annual number of patients presenting to the emergency consultations. The proportion of youths being referred for anxiety or depressive symptoms sharply increased over time, while no differences were found for the proportion of aggressive behaviors and suicidal attempts. Anxiety disorders became the most frequent discharge psychiatric disorder in youths admitted in the emergency unit, rising from 5% in 1981 to 34% in 2017. Significant changes were also observed in the source of referral to the emergency unit; in particular emergency consultations in 2017 were about twice as likely as in 1981 to be requested directly by the family. This data suggested that the increased use of emergency services observed over the last decades is associated with significant changes in the patient and his/her family’s demands about mental health difficulties. Such findings are worth considering for mental health interventions that aim to address the emergency overcrowding issue.